Finite element analysis of heat transfer in the human head / Sarfaraz Kamangar - Sarfaraz , Kamangar (2013)
Heat transfer in human body is an important issue that dictates the wellbeing of any person from health point of view. The heat is generated inside the body that has to be dissipated to outside environment based on the requirement of the body heat. The transfer of heat is controlled by a self-controlled thermoregulatory system of human body. In the current study, an investigation of heat transfer in human head is carried out by using finite element method. The 3-D geometry of human head was modeled with the help of 8 noded brick elements. Only a section of the head is modeled to take advantage of the symmetrical geometry of the head. The head is modeled with different tissues namely, skin, fat, bone and brain having varying physical and geometrical properties. The current work is focused to simulate the effect of various physical and geometrical parameters such as ambient temperature, heat transfer coefficient and variation in the thickness of different tissue layers of human head. Apart from this, the transient behavior of heat transfer in human head is investigated for situation when the person enters into a well heated car that has been parked in open sunlight. The temperature elevation of the car parked in sunlight was measured using the infrared camera. The cooling of head under severe fever condition is also investigated. It is found that the deep brain temperature remains almost constant for a wide range of environmental temperature whereas the skin temperature increases with the increase in ambient temperature but decreases with increase in the heat transfer coefficient. The effect of increased value of combined heat transfer coefficient is to reduce the temperature level in the human head. It is observed that the effect of combined heat transfer coefficient is more prominent on the outer layers of head than the brain area. It is observed that the skin temperature decreased when skin layer thickness is increased. It is found that the fat layer thickness plays the dominant role as compared to skin layer thickness in controlling the skin temperature when all other parameters are kept constant. It is observed that the temperature at most of the places of human face increases exponentially with respect to time for a person entering the car parked in sunlight for long time. The maximum temperature was found on the skin surface which is directly exposed to hot conditions. For a severe fever condition, the head can be cooled by employing an ice helmet on the section of the head that can bring down the temperature under acceptable limit after 300 seconds of cooling.